Strategi Meningkatkan Keterampilan Komunikasi Siswa dalam Pembelajaran Pendidikan Agama Islam di SMK Negeri 1 Praya - Misrahul Safitri; Syamsul Arifin; Lalu Muhammad Nurul Wathoni (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
This research aimed to find out what the strategies improve of communication skill in PAI (Islamic Religious Learning) learning at SMKN (Public Vocational High School) 1 Praya. The type of this research was field research with a qualitative approach. The data analysis method used was qualitative data analysis of interactive model from Miles and Huberman which includes data reduction, data display, and conclusion drawing/verification. The results of this study indicate that the strategies used in developing skills students in PAI learning are by using a student-centered learning approach (Student Centered Learning) or a scientific approach , presentation and discussion learning methods. The scientific approach is an approach that directs students to be able to think logically and systematically based on scientific rules and frameworks. The scientific approach is a learning approach as an implementation of the Student Centered Learning approach . Where students are given full opportunity to be active in learning and the teacher is only a facilitator. The presentation learning method is an activity of speaking in front of the class to convey information or subject matter. The discussion method is a way of presenting learning by providing opportunities for students to hold scientific conversations so that students fully participate in learning. From the results of the research that has been described, the implications of this research related to strategies for improving communication skills are: Implications for teaching methods of teachers vary, depending on what soft skills are developed. Fostering a culture of high professionalism among educational institutions and educational staff. Such as: the ability to choose and apply learning methods properly according to the learning objectives to be achieved, create interesting learning content, have good personal and social attitudes, be disciplined, and have high integrity.